Analisis Rugi-Rugi (Losses) Transformator Daya 150/20 KV di PT. PLN (Persero) Gardu Induk Sutami ULTG Tarahan - Elnizar, Hendri; Gusmedi, Herri; Zebua, Osea (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2021)
In general, in the distribution of electrical energy, there will always be losses. In a transformer, there are two types of losses, namely technical losses and non-technical losses. Non-technical losses are caused by things outside of system performance, such as accidents, natural disasters, human negligence, and so on. Meanwhile, technical losses are caused by two things, namely copper losses and core losses. Technical losses in the transformer cause the efficiency of the electricity supply to be low. Therefore the author will make a thesis entitled "Analysis of Losses Power Transformer 150/20 KV in PT PLN (PERSERO) Substation Sutami ULTG Tarahan" The analysis was carried out in July 2019, which aims to determine the amount of losses - losses on the transformer every day within a month, as well as calculating the percentage increase in losses due to changes in normal load current to peak load current. The calculation results show that the highest Losses on Transformer 1 falls on July 23, 2019, amounting to 4,588,204 kw. The highest loss on Transformer 2 falls on July 11, 2019, amounting to 16,246,884 kw. Then the magnitude of the change in the increase in current from normal load current to peak load current on Transformer 1, will cause losses to increase by 3.66 percent, and the amount of change in the increase in current from normal load current to peak load current on Transformer 2, will cause losses to increase by 2,38 percent. Keywords: Transformer, losses, copper losses, core losses